Thread: Differential equation y’’’ + 6y’’ + 12y’+ 8y = 12e^(-2x)

1. Differential equation y’’’ + 6y’’ + 12y’+ 8y = 12e^(-2x)

$y’’’ + 6y’’ + 12y’+ 8y = 12e^{-2x}$

EDIT: Hey, why don't the primes show up? Here's it without using the code
y’’’ + 6y’’ + 12y’+ 8y = 12e^(-2x)

trying using both method of undetermined coefficient & variation of parameters.

Y&rsquo;&rsquo;&rsquo; + 6y&rsquo;&rsquo; + 12y&rsquo;+ 8y = 12e^(-2x)? - Yahoo! Answers

2. Originally Posted by mathwizard
y’’’ + 6y’’ + 12y’+ 8y = 12e^(-2x)
The first step is to solve $y'''+6y''+12y'+8y = 0$ the charachteristic equation is $k^3 + 6k^2 + 12k+8 = 0$. This factors as $(k+2)^{2} = 0$. Thus, the general solution is $c_1e^{-2x}+c_2xe^{-2x}+c_3x^2e^{-2x}$. To find the particular solution we would look for a solution of the form $Ae^{-2x}$ but since this is included amongst the general we need to look for a solution of the form $Ax^3e^{-2x}$.

,

,

,

,

,

,

y'''-6y'' 12y'-8y=0

Click on a term to search for related topics.